PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG, dan PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS (Studi Pada Perusahaan Manufaktur subsektor kimia yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2018) - Tami Sriaminah; Herry Winarto (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
The purpose of this study is to examine the effect of cash turnover, receivable turnover, and inventory turnover in profitability in chemical sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2015-2018. This research is a descriptive study with a quantitative approach. The sample used is chemical sub sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2018. The number of companies used as the sample of this study is 8 companies that use Purposive sampling method. While the data analysis method used is descriptive statistical tests, testing classic assumptions, multiple linear regression analysis, Simultaneous significance test (F test), individual parameter significance test (T test) and the coefficient of determination. Based on the results of the study, cash turnover, accounts receivable turnover, and Simultaneous inventory turnover has a significant effect on profitability with a significance value of 0,000. While partially, cash turnover and inventory turnover has a significant effect on profitability with significant values ​​of 0,000 and 0,009. And the partial change of accounts receivable does not affect profitability with a significance value of 0.062.